Entwicklung eines maskenlosen Fotolithographiesystems zum Einsatz im Rapid Prototyping in der Mikrofluidik und zur gezielten Oberflächenfunktionalisierung - Waldbaur, Ansgar (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2013)
In this work, a maskless lithography device based on a micro-mirror array was designed and built. Single projection frames are seamlessly projected next to each other. Microfluidic chips of several cm² size comprising channels of 50 µm have been built of various polymers via direct lithography and casting. Also, bio-chemical ligand patterns comprising 256 different ligand densities have been created in a few seconds on a 5 mm² substrate with pixel sizes of a few µm.